Pleiotropy of cancer susceptibility variants on the risk of non-Hodgkin lymphoma: the PAGE consortium. - Unhee Lim; Jonathan M Kocarnik; William S Bush; Tara C Matise; Christian Caberto; Sungshim Lani Park; Christopher S Carlson; Ewa Deelman; David Duggan; Megan Fesinmeyer; Christopher A Haiman; Brian E Henderson; et al. (PLoS ONE)
Background Risk of non-Hodgkin lymphoma (NHL) is higher among individuals with a family history or a prior diagnosis of other cancers. Genome-wide association studies (GWAS) have suggested that some genetic susceptibility variants are associated with multiple complex traits (pleiotropy). Objective We investigated whether common risk variants identified in cancer GWAS may also increase the risk of developing NHL as the first primary cancer. Methods As part of the Population Architecture using Genomics and Epidemiology (PAGE) consortium, 113 cancer risk variants were analyzed in 1,441 NHL cases and 24,183 controls from three studies (BioVU, Multiethnic Cohort Study, Women's Health Initiative) for their association with the risk of overall NHL and common subtypes [diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), chronic lymphocytic leukemia or small lymphocytic lymphoma (CLL/SLL)] using an additive genetic model adjusted for age, sex and ethnicity. Study-specific results for each variant were meta-analyzed across studies. Results The analysis of NHL subtype-specific GWAS SNPs and overall NHL suggested a shared genetic susceptibility between FL and DLBCL, particularly involving variants in the major histocompatibility complex region (rs6457327 in 6p21.33: FL OR=1.29, p=0.013; DLBCL OR=1.23, p=0.013; NHL OR=1.22, p=5.9 × E-05). In the pleiotropy analysis, six risk variants for other cancers were associated with NHL risk, including variants for lung (rs401681 in TERT: OR per C allele=0.89, p=3.7 × E-03; rs4975616 in TERT: OR per A allele=0.90, p=0.01; rs3131379 in MSH5: OR per T allele=1.16, p=0.03), prostate (rs7679673 in TET2: OR per C allele=0.89, p=5.7 × E-03; rs10993994 in MSMB: OR per T allele=1.09, p=0.04), and breast (rs3817198 in LSP1: OR per C allele=1.12, p=0.01) cancers, but none of these associations remained significant after multiple test correction. Conclusion This study does not support strong pleiotropic effects of non-NHL cancer risk variants in NHL etiology; however, larger studies are warranted.